Cloning and characterization of cDNA encoding farnesyl disphosphate synthase from rubber tree (Hevea brasiliensis) - Adiwilaga Karthika; Kush Anil (Plant Molecular Biology, 1996)
Commercially used natural rubber (cis-1,4-polyisoprene) is a secondary matebolite of the rubber tree (Hevea brasiliensis). Previous studies have shown the involvement of a prenyl transferase in the final steps of natural rubber biosynthesis which includes polymerization of isopentenyl pyrophosphate into rubber. Using synthetic oligonucleotides corresponding to the partial amino acid sequences of this protein as probes to screen a laticifer-specific cDNA library, we have isolated a full-length cDNA which encodes a 47 kDa protein with strong homology to farnesyl diphosphate synthases from many species. The catalytic activity of this protein was confirmed by complementing the deletion yeast mutant. In Hevea, this gene is expressed in latex producing cells and in the epidermal region of the rubber plant suggesting a dual role for the protein in the biosynthesis of rubber and other isoprenoids. Although the expression level of this gene is not significantly affected by hormone treatment (e.g.ethylene), regeneration of latex due to tapping increases its expression level.
Keywords: Ethylene; Isoprenoid biosynthesis; Latex regeneration; Natural rubber; Tissue-specific gene expression